Effects of exposure to slaughter ambient on catecholamines, β-endorphin, plasma enzymes, apoptotic index and shear-force of Longissimus thoracis et lumborum muscle in goats - Kumar, P.; Abubakar, A. A.; Adewale, M. A.; Abdul, M.; Hayat, M. N.; Rahman, Md. M.; Ajat, M.; Goh, Y-M.; Kaka, U.; Sazili, A. Q. (Diponegoro University, 2025)
The present study was undertaken to evaluate the effect of exposure to the slaughter ambient on catecholamines, β-endorphin, plasma enzymes, and apoptotic index and shear-force of Longissimus thoracis et lumborum (LTL) in goats. A total of 18 goats (Boer cross bucks, 1 year age, 27.50 ±1.5 kg live weight) used in the study were divided into three groups viz. goats were slaughtered alone (Control), goats were exposed to psychological stress by exposure to the slaughter ambient (E) and goats were slaughtered in front of E goats (S). The apoptotic index of LTL muscle cells was assessed at pre-rigor state. The dressed carcass was kept in a chiller (4±1°C) for 5 days and shear force values of LTL muscle were assessed on 0-day, 1 day (24 h), and 5-day intervals. The exposure to slaughter am-bient caused a significant (p<0.05) increase in lactate dehydrogenase (LDH), nor-adrenaline, and β-endorphin levels. The apoptotic index of the E samples was recorded as significantly (p<0.05) higher than control and S samples. The apoptotic index of the S samples was significantly (p<0.05) higher than the C samples. As for the shear force, the E samples exhibited lower values (p>0.05) than the C and S samples. Thus, the present study highlights the influence of preslaughter exposure to slaughter ambient on the tenderness of LTL muscle in goats during post-mortem aging.